Injury prevention of student rock climbers based on the formation of rational technique of movements: a randomized control trial - Serhii Kozin; Zhanneta Kozina; Marina Jagiello; Marko Joksimović (Physical Education of Students)
Background and Study Aim. Students are often injured while playing sports. The main condition for preventing injuries is the correct technique of movements. In the literature, rock climbing has not been analyzed in terms of prevention of student injuries. Therefore, the development of programs to prevent injuries of students-rock climbers is relevant. Aim: to determine the impact of the use of exercises in a closed kinematic chain on the technical skill and the number of injuries to the elbows of student-rock climbers based on the analysis of the one-arm hang technique.